Generalized bullae in a young girl with KRT6A‐related pachyonychia congenita. Issue 5 (14th July 2020) - Liu, Jie; Zhong, Weilong; Yu, Bo; Lin, Zhimiao; Zheng, Yalei; Hu, Xiaoping
Abstract: Pachyonychia congenita (PC) is a rare genodermatosis showing heterogeneity with five causative keratin genes ( KRT6A, KRT6B, KRT6C, KRT16, or KRT17 ). Clinically, PC is characterized by hypertrophic onychodystrophy, painful palmoplantar keratoderma, oral leukokeratosis, and follicular hyperkeratosis. We describe an atypical case of PC in a young Chinese girl presenting with generalized bullae and identified a recurrent heterozygous missense mutation c.1406T > C (p.Leu469Pro) in KRT6A . This suggests that bullae may represent an important feature of KRT6A‐ related PC.